Analisis penyajian materi kitab An-Nahwu Al-Wadhih berdasarkan teori mackey - Amelya, Asy Syifa Reza; Tatang, Tatang; Supriadi, Rinaldi (Aksara: Jurnal Bahasa dan Sastra, 2023)
Analysis of material presentation is an activity in determining the validity and suitability of a textbook for educational institutions. In essence, textbooks are one of the factors that support the success of learning. However, another fact was found that textbooks can also be a factor causing poor learning progress. This study aims to provide an overview for educational institutions related to the textbooks studied which can be used as a reference for selecting textbooks. This research uses a qualitative approach with descriptive research type. The object of research is the book Nahwu Wadhih. Data collection techniques were carried out using library research and documentation. Data analysis was carried out using content analysis techniques. Based on the results of this study, from the selection aspect of the book Nahwu Wadhih it aims to familiarize beginners in learning Arabic through an effective model, it is common for educational institutions in Indonesia to complete learning the book Nahwu Wadih every volume for 1 academic year. Judging from the aspect of gradation, the book Nahwu Wadhih uses Rotary Gradation, the type of linguistic gradation is grammatical gradation. Judging from the presentation aspect, this book can be taught by teachers using all existing procedures. Judging from the repetition aspect, this book contains various tests in each chapter. Selection of inappropriate textbooks can cause difficulties for students and teachers. This study has limitations in the literature review because there are few studies using the same subject. For future researchers, it is advisable to carry out an analysis based on other theories as well because there is a possibility that this problem will change.Keywords: textbooks, nahwu wadhih, mackey theory